Justice and empathy : toward a constitutional ideal - Burt, Robert A., 1939-2015; Iacobucci, Frank (New Haven : Yale University Press, 2018)
The Supreme Court long considered its highest mission to be the protection of individual liberty from intrusion by government, but the court shifted its focus to social and economic equality. This text explores this shift and its implications, especially for the legal protection of the vulnerable.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 10, 2018).
Keywords: United States. -- Supreme Court; Judicial power -- United States; Constitutional law -- Social aspects -- United States; Political questions and judicial power -- United States; Sociological jurisprudence; Law; United States of America, USA; Constitution: government & the state; Laws of specific jurisdictions & specific areas of law; Legal systems: courts & procedure; Constitutional & administrative law: general